Kontrolowanie gradacji korników ( Ips typographus, Dendroctonus spp.) na obszarach chronionych w XXI wieku - Kulakowski, Dominik (Leśne Prace Badawcze, 2016)
Forests in Europe and North America are being affected by large and severe outbreaks of bark beetles (Ips typographus, Dendroctonus spp.), which have caused widespread concern about forest health and have led to proposals for tree removal in affected or susceptible forests. Any such intervention, as well as broader decisions of whether any active interventions are appropriate, should be based on the best available scientific data. This is true for all forests, including those whose purposes include timber production, watershed protection, biogeochemical function and recreation, and especially protected and conservation areas as the latter often provide particularly unique and important cultural, social, scientific and other ecosystem services. Here, I summarize peer-reviewed literature on the effects of bark beetle outbreaks and on silvicultural treatments aimed at mitigating beetle-induced tree mortality. From an objective scientific perspective, beetle outbreaks do not destroy forests. Instead, in many cases they play an important role in promoting wildlife, biodiversity and other ecological services. The best available data indicate that logging in conservation areas is unlikely to stop ongoing bark beetle outbreaks and instead may be more ecologically detrimental to the forests than the outbreaks themselves. If the purpose of a forest is timber production, then logging is desirable and can be planned based on appropriate analyses of timber yield and economic profit. However, in areas in which conservation is the determined goal, it is recommended that cutting trees be limited to removing hazards, such as trees that might fall in areas of high human activity in order to limit property damage and personal injury. Based on extensive research in Europe and North America, logging beetle-affected forests is inconsistent with most conservation goals.